2012
DOI: 10.1016/j.ptsp.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the physiotherapeutic interventions used currently after exercise-induced muscle damage: Systematic review and meta-analysis

Abstract: Introduction: Exhaustive and/or unaccustomed exercise, mainly involving eccentric muscle actions, induces temporary muscle damage, evidenced by delayed onset muscle soreness (DOMS) and decreased muscle function. Different strategies to recover from its signs and symptoms have been studied and, as a result, a significant number of articles on this issue have been published.Objective: To assess whether some modalities currently used in physiotherapy such as massage, cryotherapy, stretching and low-intensity exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 51 publications
2
91
0
5
Order By: Relevance
“…Correspondingly stretching was reported as the most commonly used recovery strategy in the present study; however stretching was not most frequently reported as the most beneficial recovery strategy. This belief that stretching is not the 18 most beneficial recovery strategy available is consistent with a recent systematic review and meta-analysis, which reported that there is no robust scientific evidence to support the use of stretching in reducing muscle soreness or improving muscle recovery after exercise-induced muscle damage [4]. The reasons why runners continue to use stretching, despite an awareness that its benefits may be limited, were not investigated in the present study.…”
Section: Reasons For Using Recovery Strategiessupporting
confidence: 75%
See 1 more Smart Citation
“…Correspondingly stretching was reported as the most commonly used recovery strategy in the present study; however stretching was not most frequently reported as the most beneficial recovery strategy. This belief that stretching is not the 18 most beneficial recovery strategy available is consistent with a recent systematic review and meta-analysis, which reported that there is no robust scientific evidence to support the use of stretching in reducing muscle soreness or improving muscle recovery after exercise-induced muscle damage [4]. The reasons why runners continue to use stretching, despite an awareness that its benefits may be limited, were not investigated in the present study.…”
Section: Reasons For Using Recovery Strategiessupporting
confidence: 75%
“…The effectiveness of such recovery strategies does however appear to vary widely. For example recent meta-analyses investigating post-exercise recovery strategies have concluded that the use of compression garments [2] and cold water immersion [3] are beneficial, but that there is insufficient evidence to support the use of stretching [4] or contrast immersion [3].…”
Section: Introductionmentioning
confidence: 99%
“…Torres et al (2012) reported that massage applied after exercise is effective on muscle soreness only after 24h post exercise. This confirms the recommendation of Tiidus (1997) who showed that massage also had an effect on inflammatory response and may be able to affect the later development of muscle soreness.…”
Section: Doms and Systemic Markers Of Inflammationmentioning
confidence: 99%
“…By the way, these results have been inconsistency effect on muscle soreness sensation and muscle performance yet (Sellwood et al, 2007;Jakeman, Macrae & Eston, 2009;Howatson, Goodall & Someren, 2009;Goodall & Howatson, 2008;Torres et al, 2012).…”
Section: Introductionmentioning
confidence: 98%